Impact of Arterial CO2 Retention in Patients With Moderate or Severe ARDS. - Maamar, Adel; Delamaire, Flora; Reizine, Florian; Lesouhaitier, Mathieu; Painvin, Benoit; Quelven, Quentin; Coirier, Valentin; Guillot, Pauline; Le Tulzo, Yves; Tadié, Jean Marc; Gacouin, Arnaud (Respiratory Care, 2023)
Background: Lung-protective ventilation (reduced tidal volume and limited plateau pressure) may lead to CO2 retention. Data about the impact of hypercapnia in patients with ARDS are scarce and conflicting. Methods: We performed a non-interventional cohort study with subjects with ARDS admitted from 2006 to 2021 and with PaO2 /FIO2 ≤ 150 mm Hg. We examined the association between severe hypercapnia (PaCO2 ≥ 50 mm Hg) on the first 5 days after the diagnosis of ARDS and death in ICU for 930 subjects. All the subjects received lung-protective ventilation. Results: Severe hypercapnia was noted in 552 subjects (59%) on the first day of ARDS (day 1); 323/930 (34.7%) died in the ICU. Severe hypercapnia on day 1 was associated with mortality in the unadjusted (odds ratio 1.54, 95% CI 1.16-1.63; P = .003) and adjusted (odds ratio 1.47, 95% CI 1.08-2.43; P = .004) models. In the Bayesian analysis, the posterior probability that severe hypercapnia was associated with ICU death was > 90% in 4 different priors, including a septic prior for this association. Sustained severe hypercapnia on day 5, defined as severe hypercapnia present from day 1 to day 5, was noted in 93 subjects (12%). After propensity score matching, severe hypercapnia on day 5 remained associated with ICU mortality (odds ratio 1.73, 95% CI 1.02-2.97; P = .047). Conclusions: Severe hypercapnia was associated with mortality in subjects with ARDS who received lung-protective ventilation. Our results deserve further evaluation of the strategies and treatments that aim to control CO2 retention.